Derivados do eugenol e isoeugenol e suas potencialidades antifúngica e antibiofilme - Jardim, Jeane Uilma Galindo (2019)
This work describes the synthesis, characterization and antifungal potential and antibiofilm of eighteen monoterpene derivatives, nine of which are derived from eugenol and nine from isoeugenol. The synthesis of these compounds, which yielded satisfactory yields (74 to 92%), occurred in two steps: nine acetamides were initially synthesized and then these were derivatized with eugenol and isoeugenol separately in an etherification reaction of type SN2. All compounds, acetamides and derivatives were characterized by IR spectroscopic techniques, 1 H and 13 C NMR and the antifungal potential of the derivatives against Candida albicans strains and antibiofilm activity against Escherichia coli and Staphilococcus aureus were evaluated. Among the eighteen derivatives investigated, antifungal studies indicated that isoeugenol (E) 2- (2-methoxy-4- (prop-1-en-1-yl) phenoxy) -N-phenylacetamide and (E) - N- (4chlorophenyl) -2- (2-methoxy-4- (prop-1-en-1-yl) phenoxy) acetamide and the eugenol derivative 2- (4-allyl-2-methoxyphenoxy) -N- (4-allyl-2-methoxyphenyl) -N- (4-chloro-3-nitrophenyl) acetamide showed a strong inhibitory activity of 85 % of strains of the genus Candida. Anti-adherent activity was observed in six of the ten isoeugenol derivatives against E. coli, and the adhesion of only 2.9% of the isoeugenol (E) -2- (2-methoxy-4- (prop-1- en-1-yl) phenoxy) -N-phenylacetamide. For S. aureus, derivatives of isoeugenol (E) -N- (4-ethylphenyl) -2- (2-methoxy-4- (prop-1-en-1-yl) phenoxy) acetamide and (E) -2- (2-methoxy-4- (prop-1-en-1-yl) phenoxy) -N- (p-tolyl) acetamide exhibited excellent non-stick activity of less than 10%, and eugenol derivatives showed non-stick activity between 3.72 and 90.43%. All eugenol derivatives showed less than 10% antibiofilm activity against E. coli. Antibacterial studies showed that the lowest MIC was observed in the compound (E) 2- (2-methoxy-4- (prop-1-en-1-yl) phenoxy) -N- (4-methoxyphenyl) acetamide E. coli (35 μg / mL) and 2- (4-allyl-2-methoxyphenoxy) -N- (4-chloro-3-nitrophenyl) acetamide (66.8 μg / mL) for S. aureus. Quantitative Structure-Activity Relationships (QSAR) studies indicated that the descriptors that contributed significantly and positively to the isoeugenol series are DIFF (diffusivity, control of chemical dispersion in water at 25 ° C) and CP (critical packaging parameter) , whereas for the eugenol series only the descriptor V (molecular volume) which influences increasing, that is, a larger volume in an aqueous solution and greater repulsion to water results in considerable antifungal activity.